Innovative nano-solution: Biosynthesized nickel oxide nano-particles (NPs) protect carrot roots from root knot nematode, Meloidogyne incognita infestation - Sherin, Shana; Rizvi, Rose; Fatima, Noor; Parveen, Muskan; K P, Jaseem; V, Ameer Favas; E S, Mubeena (International Journal of Environment, Agriculture and Biotechnology, 2024)
Carrot (Daucus carota L.) is a crucial horticultural crop globally, valued for its nutritional benefits and economic significance. However, it faces substantial challenges from plant-parasitic nematodes, particularly Meloidogyne incognita, which significantly impact yield and quality. In this study, we examined the effect of Meloidogyne incognita (MI) infected carrot plants, that were treated separately with Ocimum santum leaves extract, Nickel sulphate salts and Nickel oxide nanoparticles (NiO-NPs) at different concentration (10, 50, 250, 500, 750 & 1000 ppm) as a pot set experiment. The result focused on the plant physiological, growth and nematode related parameters of MI inoculated plants that were treated with 1000 ppm verses the controlled untreated one. It shows significant plant growth in shoot length increased by 35.47%, root length by 266.4%, shoot fresh weight by 724%, root fresh weight by 631.2%, shoot dry weight by 819%, and root dry weight by 560.1% and the Physiological parameters shows improvement in total chlorophyll content 115% and carotenoid content decreased by 61.26% compared to the untreated control. Substantial reduction in the activity of nematode population per soil, gall formation and eggs per egg mass indicates promising applications of green-synthesized NiO NPs at 1000 ppm as sustainable agents for managing nematode infestations in carrot cultivation, there by contributing to enhanced crop productivity and sustainability in agriculture.